Integrated pest and pollinator management in India: A way forward to sustainable agriculture - MUKHTAR, YOUSRA; SHANKAR, UMA (The Indian Journal of Agricultural Sciences, 2023)
Pollinators play a vital role in sustaining both cultivated and wild plants, thus ensuring the well-being of humanity. Unfortunately, the indiscriminate methods employed in pest-management have a detrimental impact on beneficial fauna, especially pollinators. Taking into account the harmful effects of pesticides on pollinators and the lack of explicit consideration for their welfare in Integrated Pest Management (IPM) practices, there is an urgent need to integrate pollinator management into the IPM programme. Incorporating pollinator management within the IPM framework is essential for maintaining the health of pollinators, preserving diverse pollinator species and achieving optimal crop yields with reduced pest-related issues- aspects that are often overlooked in conventionalpest management approaches. This transformation from IPM to IPPM (Integrated Pest and Pollinator Management) highlights the importance of selectively and judiciously employing pesticides and other pest control strategies that have minimal impact on the habits, habitats, reproductive capabilities, foraging behaviour, growth, development and survival of pollinators. Although the concept of IPPM was introduced by Biddinger and Rajote (2015), our focus lies in explaining its relevance within the Indian context. Here, IPPM is imperative for reducing pest populations below economically damaging thresholds while simultaneously enhancing and conserving pollinators. By achieving this delicate balance, the ecological equilibrium can be preserved, ensuring the continued existence of various species and sustainability of our ecosystem.